2011
DOI: 10.1128/jcm.00224-11
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Respiratory Viruses by PCR Assay of Nasopharyngeal Swabs Stored in Skim Milk-Tryptone-Glucose-Glycerol Transport Medium

Abstract: We analyzed 129 paired nasopharyngeal aspirates (stored in viral transport medium [VTM]) and nasopharyngeal swabs (stored in skim milk-tryptone-glucose-glycerol [STGG] bacterial transport and storage medium) using PCRs to detect adenoviruses, influenza virus A or B, and respiratory syncytial virus (RSV). Overall, swabs stored in STGG medium without antimicrobials were found to be an acceptable alternative to aspirates stored in antimicrobial-containing VTM, with PCR agreement of 90.2% (kappa of 0.8).Longitudin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…11 Our study, which used samples from young Andean children with acute respiratory illness, complements the prior report and expands it to a larger number of samples including MPV, HRV and PIV3; NS samples, which are commonly obtained; and importantly, by comparing CT values between detection strategies. Notably, even though our NP samples had undergone a previous freeze-thaw cycle, the detection of viruses was remarkably similar between the 2 sampling strategies.…”
Section: Discussionmentioning
confidence: 70%
“…11 Our study, which used samples from young Andean children with acute respiratory illness, complements the prior report and expands it to a larger number of samples including MPV, HRV and PIV3; NS samples, which are commonly obtained; and importantly, by comparing CT values between detection strategies. Notably, even though our NP samples had undergone a previous freeze-thaw cycle, the detection of viruses was remarkably similar between the 2 sampling strategies.…”
Section: Discussionmentioning
confidence: 70%
“…(22, 26-29) Despite different collection methods, prior studies by our group and others have demonstrated a very high agreement (89%-99%) in the detection of common respiratory viruses between NS and NP samples collected in this manner. (16, 30) For samples with virus detections, RT-PCR cycle thresholds (CT) from asymptomatic and ARI periods were considered as surrogates for viral loads, with higher CT indicating lower viral load. CT values of ≤40 were used to define sample positivity.…”
Section: Methodsmentioning
confidence: 99%
“…18 During the course of the vaccine trial, 1888 pernasal swabs were collected from 319 young children. Swabs were collected into 1 mL of skim milk-tryptoneglucose-glycerin-broth (STGGB) 19 and stored at −80 • C. A limited number of those samples collected between January 2006 and August 2008 were shipped to Perth, Western Australia for viral studies. Those samples included 80 from young children with ALRI and 273 from children with no evidence of ALRI.…”
Section: Methodsmentioning
confidence: 99%